The transcriptional regulator gene E2 of the Human Papillomavirus (HPV) 16 influences the radiosensitivity of cervical keratinocytes - Lindel, Katja; Rieken, Stefan; Daffinger, Sigrid; Weber, Klaus-Josef; Villiers, Ethel-Michele de; Debus, Jürgen (Radiation oncology, 2012)
Clinical studies have demonstrated that HPV induced tumors constitute a specific subclass of cancer with a better response to radiation treatment. The purpose of this study was to investigate meaning of viral E2-gene for radiosensitivity. W12 cells contain episomal HPV 16 genomes, whereas S12 cells, which derive from the W12 line, contain HPV DNA as integrated copies. Clonogenic survival was analyzed using 96-well in vitro test. Using flow cytometry cell cycle analyses were performed. Expression of pRb and p53 were analyzed using intracellular staining. W12 cells (intact E2 gene) showed a lower survival fraction than S12 cells. W12 cells developed a G2/M block 24 h after irradiation with 2 Gy whereas S12 showed no G2/M bloc. After irradiation S12 cells developed polyploidy and pRb-positive cells decreased. W12 cells showed no change of pRb-positive cells. Depending on E2 gene status differences in cell cycle regulation might cause radioresistance. The E2/E7/pRb pathway seems to influence HPV-induced radiosensitivity. Our experiments demonstrated an effect of HPV on radiosensitivity of cervical keratinocytes via viral transcription regulator E2 pathway.
Gesehen am 16.11.2018